Youth Enjoy Science Program at the Case Comprehensive Cancer Center: Increasing Engagement and Opportunity for Underrepresented Minority Students. - Qua, Kelli; Papp, Klara K.; Junk, Damian J.; Webb Hooper, Monica; Berger, Nathan A. (Ethnicity & Disease)
The Youth Enjoy Science (YES) Program at the Case Comprehensive Cancer Center is a National Cancer Institute (NCI) R25-funded training grant, designed to increase the pipeline of underrepresented minority (URM) students entering college and pursuing biomedical research and health care careers in the Cleveland Metropolitan and surrounding school districts. The three components of the program include: Learn to Beat Cancer, engaging middle school students and their families; Research to Beat Cancer, designed for high school students and college undergraduates; and Teach to Beat Cancer, focused on enhancing science, technology, engineering, and mathematics (STEM) teaching capacity among high school teachers. This study focuses on Research to Beat Cancer, which, in 2018 enrolled 36 URM students as paid summer scholars. Students were assigned to a faculty mentor, were taught laboratory safety, responsible conduct of research and the scientific method, and then immersed in full-time laboratory cancer research during an eight-week period. Twice each week, students participated in Lunch and Learn Seminars where faculty members provided combined motivational and scientific guidance lectures. In a capstone poster session at the end of the program, students presented their research to peers, medical and graduate students, family members, faculty, community members and leaders. Students' perceptions of the program were reported using descriptive statistics and qualitative thematic analyses. Twenty-four of the 2018 YES students (67%) and 19 (53%) mentors completed the online post-program survey. Opportunity was a major qualitative theme from student and mentor responses. Future research will investigate the long-term impacts of YES, including college enrollment.